Blockchain-Based Digital Transformation in Government Administration System - Rustiyana Rustiyana (Pt. Anagata Sembagi Education, 2025)
Digital transformation in government administration systems is key to increasing transparency, efficiency, and accountability in public services. The implementation of blockchain technology offers an innovative solution by providing secure, decentralized, and immutable transaction records. This study aims to analyze the role of blockchain in strengthening government administration processes and evaluate its impact on operational performance and public trust. The research method used is a comprehensive literature review and case analysis of blockchain implementation in several local governments and public institutions. The results show that blockchain integration can reduce bureaucracy, improve data security, and promote transparency, but requires the readiness of digital infrastructure and supporting regulations. These findings provide guidance for policymakers and IT practitioners in developing blockchain-based digital transformation strategies in the public sector.